Analysis of a professional development on its learning environments. (2014) - Chien, Chin-Wen
Bransford et al. (2000) asserted that high-quality learning environments for teachers' learning should be centred on learners, knowledge, assessments and community. This study aims to use Bransford et al.'s (2000) concept of high-quality learning environments to analyse a 5-day Collaborative Summer Institute (CSI) in terms of its design and delivery of professional development. The data in this study includes: (1) workshop binders and handouts; (2) observational notes and (3) documentation. The study concludes that the CSI could be regarded as a learner-centred, a knowledge-centred and community-centred environment. The CSI was considered in part to be an assessment-centred environment because participating teachers were asked to evaluate their learning outcomes at the end of each training session. Bransford et al.'s (2000) perspectives on effective learning environments, however, offered no means of evaluating whether the CSI was assessment-centred. Suggestions on the effective design and delivery of professional development will be provided.